An enantiospecific synthesis of 5-epi-α-bulnesene - Zong, J; Robertson, J (MDPI, 2023)
As a result of its unique fragrance and wider role in traditional medicine, agarwood produced in Aquilaria spp. and certain other trees has been harvested to near extinction as a natural phenomenon. Artificially induced agarwood production in Aquilaria plantations has sated some of the demand although the product quality is variable. Synthetic chemistry may have a role to play in providing sustainable routes to many of the fragrant components identified in agarwood and its smoke when burnt as incense. In this work, we report efforts towards a total synthesis of the guaiane sesquiterpene α-bulnesene, which is found, along with its more fragrant oxidised derivatives, in agarwood. Following the ring-expansion of (R)-carvone using reported procedures, α-butenylation gave a substrate for samarium diiodide mediated reductive cyclisation, the two butenyl epimers of the substrate each leading to a single bicyclic alcohol (24 and 25). Overall homoconjugate hydride reduction of one of these alcohols was achieved by Lewis acid-mediated ionisation and then hydride transfer from triethylsilane to complete an overall seven-step synthesis of 5-epi-α-bulnesene. This new synthesis paves the way for short routes to both α-bulnesene enantiomers and a study of their aerial and enzymatic oxidation products.